Analysis of Asphericity and Corneal Longitudinal Spherical Aberration of 915 Chinese Myopic Adult Eyes - Zhang J; Zheng L; Zhang Y; Wang K (Clinical Ophthalmology, 2023)
Jun Zhang, Li Zheng, Yixuan Zhang, Ke Wang Department of Ophthalmology, Hangzhou MSK Eye Hospital, Hangzhou, People’s Republic of ChinaCorrespondence: Jun Zhang, Department of Ophthalmology, Hangzhou MSK Eye Hospital, Hangzhou, People’s Republic of China, Tel +86-18667046602 ; +86-0571 85064148, Email zhangjun@mskyk.onaliyun.comPurpose: To analyze the corneal asphericity, longitudinal spherical aberration (LSA), and related factors in Chinese myopic adult eyes.Methods: This was a retrospective study of myopic adult patients. The corneal asphericity and LSA were measured at 3.0, 4.0, 5.0, 6.0, and 7.0 mm diameter apertures using corneal tomography. Age and refractive power were recorded for correlation analysis.Results: In total, 531 females and 384 males were included. At the above five diameter settings the corneal asphericity values (Q) of the anterior surface were − 0.09± 0.21, − 0.14± 0.16, − 0.15± 0.13, − 0.17± 0.11, and − 0.20± 0.11, and those of the posterior surface were 0.23± 0.49, 0.06± 0.29, − 0.01± 0.22, − 0.07± 0.16, and − 0.08± 0.15, respectively. The anterior corneal LSA values at these diameters were 0.39± 0.19, 0.63± 0.27, 0.97± 0.36, 0.90± 0.30, and 0.83± 0.29 D, respectively and the whole corneal values were 0.26± 0.20, 0.44± 0.27, 0.70± 0.36, 0.66± 0.30, and 0.59± 0.28 D, respectively. Corneal asphericity and peripheral LSA showed no or weak correlation with age or spherical equivalent (all r < 0.2).Conclusion: Corneal anterior and posterior Q values in myopia patients are negatively correlated with corneal diameter. Corneal anterior and whole corneal LSA increased significantly with diameter up to 5 mm, then decreased slightly with diameter. Corneal asphericity and peripheral LSA showed very weak or no correlation with age or spherical equivalent.Clinical Trial Registration Number: ChiCTR1800015985.Keywords: wavefront aberration, asphericity, longitudinal spherical aberration, myopia